Islam: antara Idealita dan Realita - M. Irfan; Roibin Roibin (el Harakah: Jurnal Budaya Islam, 1999)
The actual discourse of religion which has ceased only in the plains of discourse (ideality) and religion as a necessity to apply (reality), has historically centered on the plurality of religions from time to time. Furthermore, there are several works that have colored the minds of scientists lately, not to mention the growing fertile repertoire of Islamic thought. This is one of the consequences of a serious debate on Islam at the level of indeal and reality. This discourse seems to be not only a great event in the field of science that passes by, but it is very meaningful for the followers of religion to further be used as a consideration in positioning their respective diversity. The development of religion will all depend on the intellectual capability of the religious adherents of their adherents. If religious observations are packed and articulated exclusively, then the visible religion will have a scary and frightening face. This is what is popularly referred to as religious fundamentalism. Diskursus aktual seputar agama yang hanya berhenti dalam dataran wacana (idealita) dan agama sebagai sebuah keharusan untuk diaplikasikan (realita), telah mensejarah di tengah-tengah pluralitas agama-agama sejak dahulu hingga kini. Lebih jauh, muncul beberapa karya yang telah mewarnai corak pemikiran para ilmuwan belakangan ini, belum lagi tumbuh suburnya khasanah pemikiran umat Islam yang silih berganti. Hal ini merupakan salah satu akibat perdebatan serius mengenai Islam pada tataran antara indealita dan realita. Diskursus ini nampaknya tidak saja merupakan perhelatan akbar di bidang keilmuan yang lewat begitu saja, namun ia sangat memberikan arti bagi pemeluk agama untuk selanjutnya dijadikan sebagai pertimbangan dalam memposisikan sikap keberagaman mereka masing-masing. Perkembangan agama semuanya akan sangat bergantung pada daya tangkap intelektual penghayatan keagamaan para pemeluknya. Jika penghayatan keagamaan itu dikemas dan diartikulasikan secara eksklusif, maka agama yang tampak akan berwajah yang seram dan menakutkan. Cara inilah yang populer disebut sebagai fundamentalisme agama.